Exploring the role of OIP5-AS1 in the mechanisms of delayed fracture healing: functional insights and clinical implications - Yusen Hu; Meini Cen; Yi Hu (Journal of Orthopaedic Surgery and Research)
Abstract Objective Fracture is a common traumatic disease and there is a risk of delayed healing after fracture occurs. This study aimed to explore the regulatory roles and clinical implications of OIP5-AS1 in delayed fracture healing. Methods The study included 80 normal fracture healing patients and 80 delayed fracture healing patients. RT-qPCR was used to assess the levels of OIP5-AS1 and miR-7-5p in the serum of patients and MC3T3-E1 cells. The ROC curve was utilized to evaluate the predictive value of OIP5-AS1 for delayed fracture healing. Dual-luciferase reporter assays and RIP assays were conducted to validate the interaction between OIP5-AS1 and miR-7-5p. Cell viability and apoptosis were determined by CCK-8 and flow cytometry. Results OIP5-AS1 was abnormally elevated in the serum of delayed fracture healing patients, and OIP5-AS1 had a predictive value for delayed fracture healing. Cell experiments demonstrated that overexpression of OIP5-AS1 significantly inhibited osteogenic differentiation, reduced cell viability, and stimulated apoptosis. miR-7-5p was identified as the target miRNA of OIP5-AS1 and was negatively regulated by OIP5-AS1. Furthermore, transfecting with miR-7-5p mimic significantly alleviated the inhibitory effect of OIP5-AS1 on osteoblast activity. Conclusion OIP5-AS1 was identified as a potential biomarker for predicting delayed fracture healing. Additionally, it could inhibit fracture healing through the sponge effect on miR-7-5p.